Research on the Impact of Investment in Technological Innovation on Financial Competitiveness of Agricultural Listed - Yang, Xinyu (International Journal of Global Economics and Management, 2024)
Agricultural listed company is the leading force in the agricultural industry, its sustainable development can not be separated from the support of technological innovation, and its technological innovation ability determines whether the enterprise can realize the maximum value, the financial competitiveness of enterprises as an important part of the core competitiveness. Therefore, this paper takes agricultural listed companies as the research object, analyzes the impact of their investment in technological innovation on their financial competitiveness, and provides empirical basis for the management to formulate industrial policy, thus promote the optimization and upgrading of China's agricultural industrialization, enhance its financial competitiveness, improve the value of enterprises.